2022
DOI: 10.3390/chemosensors10080299
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Area on Sensitivity in Autonomously Reporting Sensing Hydrogel Nanomaterials for the Detection of Bacterial Enzymes

Abstract: The rapid and selective detection of bacterial contaminations and bacterial infections in a non-laboratory setting using advanced sensing materials holds the promise to enable robust point-of-care tests and rapid diagnostics for applications in the medical field as well as food safety. Among the various possible analytes, bacterial enzymes have been targeted successfully in various sensing formats. In this current work, we focus on the systematic investigation of the role of surface area on the sensitivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Thus, for this type of sensor, the characteristics of the sensitive layer directly influence the sensor results. It has been demonstrated that the greater the specific surface area of the film, the greater the sensitivity of the sensor [8]. Consequently, the use of nanoparticles (NPs) or porous layers in the production of SAW sensors leads to an improvement in their performances.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for this type of sensor, the characteristics of the sensitive layer directly influence the sensor results. It has been demonstrated that the greater the specific surface area of the film, the greater the sensitivity of the sensor [8]. Consequently, the use of nanoparticles (NPs) or porous layers in the production of SAW sensors leads to an improvement in their performances.…”
Section: Introductionmentioning
confidence: 99%